2008
DOI: 10.1103/physrevlett.101.027002
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Thin Films of Boron-Doped Carbon Nanotubes

Abstract: Superconductivity in carbon nanotubes (CNTs) is attracting considerable attention. However, its correlation with carrier doping has not been reported. We report on the Meissner effect found in thin films consisting of assembled boron (B)-doped single-walled CNTs (B-SWNTs). We find that only B-SWNT films consisting of low boron concentration leads to evident Meissner effect with Tc=12 K and also that a highly homogeneous ensemble of the B-SWNTs is crucial. The first-principles electronic-structure study of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 20 publications
2
48
0
2
Order By: Relevance
“…Recently Murata et al ͑2008͒ reported the observation of the Meissner effect at T c = 12 K in thin films of CB y -SWNTs synthesized with the laser vaporization technique. They pointed out that the Meissner effect was sensitive to the degree of uniformity of the thin film and that by optimizing the control of the deposition of the films higher T c values ͑between 30 and 40 K͒ could be reached.…”
Section: Transportmentioning
confidence: 99%
“…Recently Murata et al ͑2008͒ reported the observation of the Meissner effect at T c = 12 K in thin films of CB y -SWNTs synthesized with the laser vaporization technique. They pointed out that the Meissner effect was sensitive to the degree of uniformity of the thin film and that by optimizing the control of the deposition of the films higher T c values ͑between 30 and 40 K͒ could be reached.…”
Section: Transportmentioning
confidence: 99%
“…Also there are theoretical studies related to superconductivity in doped SWCNT [111] experimental studies are rare for intercalated SWCNT. Superconductivity in B-doped SWCNT was claimed to be up to a T c of 12 K [112], for SWCNT in zeolites a T c of 15 K was shown [113].…”
Section: Feature Articlementioning
confidence: 99%
“…Besides the well-known Luttinger liquid (LL) state, intrinsic superconductivity has been experimentally observed or theoretically predicted in SWCNTs, [1][2][3][4][5][6][7][8][9][10][11][12][13] CNT ropes, [14][15][16][17] multiwall CNTs (MWCNTs), [18][19][20][21][22][23] and doped CNTs. [24][25][26][27] For the case of ultrathin diameter 4-Angstrom metallic SWCNTs, experimental observation of the Meissner effect in 2001 1 has prompted some theoretical works exploring the possibility of superconductivity being the ground state of the system. While some authors predicted Peierls ground state, [28][29][30][31][32] others predicted superconductivity.…”
Section: Introductionmentioning
confidence: 99%